Perancangan dan Implementasi Sistem Pembimbing Akademik Berbasis Website Metode Agile - Candra Irawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
One of the many problems faced by a university is the potential for students to drop out. Therefore, it is necessary to have a system to map students who are threatened with dropping out and then solve the problems that these students have. The purpose of the development of this Academic Advisor System web application is to create an Academic Advisor System web in guiding students who are indicated to have problems and require guidance. The method used is experimental with the Agile Method approach. The final result of the development of the Academic Advisor System web application facilitates all mentoring processes starting from the student search stage, the appointment of academic supervisors, scheduling mentoring, implementing mentoring, to reporting mentoring. The conclusion of this research is that the academic advising system web that has been created has the opportunity to reduce the dropout rate of students with ease and efficiency in using the web.